Narrative Review of Digital Literacy Curriculum Implementation in Early Childhood Education - Betty Fitriani; Dian Yahya; Indrawati Setyaningrum (JINEA: Journal of Innovation in Education and Learning, 2025)
This study examines the integration of digital literacy into early childhood education (ECE) through a socio-cultural and policy-aligned lens. Employing a qualitative document analysis and framework synthesis, policy documents from Indonesia and international organizations were reviewed alongside research on child development and pedagogical innovation. Findings reveal that effective digital literacy implementation requires culturally responsive strategies, equitable access, and alignment with national and international policies. The proposed framework emphasizes staged integration, play-based learning, teacher competency, family engagement, and community partnerships. Practical implications highlight that digital literacy is a transformative component bridging theory and practice, fostering holistic child development and preparing children for the digital age. Challenges include infrastructure disparities, limited assessment tools, and privacy concerns, necessitating targeted policy interventions and professional development. This study provides actionable guidance for curriculum designers and policymakers to ensure inclusive and effective digital literacy adoption in ECE.